Antifibrotic effects of specific targeting of the 5-hydroxytryptamine 2B receptor (5-HT2BR) in murine models and ex vivo models of scleroderma skin - Trinh-Minh, Thuong; Tran-Manh, Cuong; Györfi, Andrea Hermina; Dickel, Nicholas; Liebel, Christoph; Zhou, Xiang; Wang, Jiucun; Kunz, Meik; Arozenius, Helena; Pettersson, Lars; Lindgren, Sam; Wenglén, Christina; et al. (Arthritis and Rheumatology, 2025)
Objective: Systemic sclerosis (SSc) is a connective tissue disease with fibrotic remodeling of the skin and various internal organs. SSc is associated with the highest case-specific mortality of all rheumatic autoimmune diseases with limited antifibrotic treatment options. Here, we evaluated the therapeutic effects of the highly selective 5-hydroxytryptamine 2B receptor (5-HT2BR) inhibitor AM1476. Methods: The antifibrotic effects of AM1476 were evaluated in the mouse models of bleomycin-induced pulmonary fibrosis in Tsk-1 mice and in mice with sclerodermatous chronic graft-versus-host disease. For further validation, the antifibrotic effects of AM1476 were analyzed in precision cut skin (PCS) slices from patients with SSc. Results: AM1476 demonstrated high selectivity for 5-HT2BR over more than 200 other receptors, including other 5-HT receptors in vitro. AM1476 reduced accumulation of hydroxyproline and fibrotic tissue remodeling of skin and/or lungs in all three mouse models at well-tolerated doses with a comparable efficacy to that of nintedanib. In PCS of SSc skin, treatment with AM1476 reduced the expression of SSc-specific signature genes. AM1476 demonstrated more pronounced regulation of terms related to fibroblast activation and fibrotic remodeling than mycophenolate mofetil. Conclusion: We describe AM1476 as a highly selective inhibitor of 5-HT2BR. Treatment with AM1476 ameliorated fibrosis in three mouse models of SSc and normalized the expression of fibrosis-related genes directly in SSc skin. Because AM1476 also demonstrated good tolerability in a phase 1 trial, further clinical trials with AM1476 are currently in the planning stage.
CRIS-Team Scopus Importer:2025-05-30

Artificial Intelligence Identifies an Urgent Need for Peripheral Vascular Intervention by Multiplexing Standard Clinical Parameters - Sonnenschein, Kristina; Stojanovic, Stevan D.; Dickel, Nicholas; Fiedler, Jan; Bauersachs, Johann; Thum, Thomas; Kunz, Meik; Tongers, Joern (Biomedicines, 2021)
Background: Peripheral artery disease (PAD) is a significant burden, particularly among patients with severe disease requiring invasive treatment. We applied a general Machine Learning (ML) workflow and investigated if a multi-dimensional marker set of standard clinical parameters can identify patients in need of vascular intervention without specialized intra-hospital diagnostics. Methods: This is a retrospective study involving patients with stable PAD (sPAD, Fontaine Class I and II, n = 38) and unstable PAD (unPAD, Fontaine Class III and IV, n = 18) in need of invasive therapeutic measures. ML algorithms such as Random Forest were utilized to evaluate a matrix consisting of multiple routinely clinically available parameters (age, complete blood count, inflammation, lipid, iron metabolism). Results: ML has enabled a generation of an Artificial Intelligence (AI) PAD score (AI-PAD) that successfully divided sPAD from unPAD patients (high AI-PAD in sPAD, low AI-PAD in unPAD, cutoff at 50 AI-PAD units). Furthermore, the probability score positively coincided with gold-standard intra-hospital mean ankle-brachial index (ABI). Conclusion: AI-based tools may be promising to enable the correct identification of patients with unstable PAD by using existing clinical information, thus supplementing clinical decision making. Additional studies in larger prospective cohorts are necessary to determine the usefulness of this approach in comparison to standard diagnostic measures.
CRIS-Team WoS Importer:2021-11-19

Attenuation of fibroblast activation and fibrosis by adropin in systemic sclerosis - Liang, Minrui; Dickel, Nicholas; Györfi, Andrea Hermina; SafakTümerdem, Bilgesu; Li, Yi Nan; Rius Rigau, Aleix Rius; Liang, Chunguang; Hong, Xuezhi; Shen, Lichong; Matei, Alexandru-Emil; Trinh-Minh, Thuong; Tran-Manh, Cuong; et al. (Science Translational Medicine, 2024)
Fibrotic diseases impose a major socioeconomic challenge on modern societies and have limited treatment options. Adropin, a peptide hormone encoded by the energy homeostasis–associated (ENHO) gene, is implicated in metabolism and vascular homeostasis, but its role in the pathogenesis of fibrosis remains enigmatic. Here, we used machine learning approaches in combination with functional in vitro and in vivo experiments to characterize adropin as a potential regulator involved in fibroblast activation and tissue fibrosis in systemic sclerosis (SSc). We demonstrated consistent down-regulation of adropin/ENHO in skin across multiple cohorts of patients with SSc. The prototypical profibrotic cytokine TGFβ reduced adropin/ENHO expression in a JNK-dependent manner. Restoration of adropin signaling by therapeutic application of bioactive adropin34–76 peptides in turn inhibited TGFβ-induced fibroblast activation and fibrotic tissue remodeling in primary human dermal fibroblasts, three-dimensional full-thickness skin equivalents, mouse models of bleomycin-induced pulmonary fibrosis and sclerodermatous chronic graft-versus-host-disease (sclGvHD), and precision-cut human skin slices. Knockdown of GPR19, an adropin receptor, abrogated the antifibrotic effects of adropin in fibroblasts. RNA-seq demonstrated that the antifibrotic effects of adropin34–76 were functionally linked to deactivation of GLI1-dependent profibrotic transcriptional networks, which was experimentally confirmed in vitro, in vivo, and ex vivo using cultured human dermal fibroblasts, a sclGvHD mouse model, and precision-cut human skin slices. ChIP-seq confirmed adropin34–76-induced changes in TGFβ/GLI1 signaling. Our study characterizes the TGFβ-induced down-regulation of adropin/ENHO expression as a potential pathomechanism of SSc as a prototypical systemic fibrotic disease that unleashes uncontrolled activation of profibrotic GLI1 signaling.
CRIS-Team Scopus Importer:2024-04-05

Combined inhibition of IL-1, IL-33 and IL-36 signalling by targeting IL1RAP ameliorates skin and lung fibrosis in preclinical models of systemic sclerosis - Grönberg, Caitríona; Rattik, Sara; Tran-Manh, Cuong; Zhou, Xiang; Rius Rigau, Aleix Rius; Li, Yi Nan; Györfi, Andrea Hermina; Dickel, Nicholas; Kunz, Meik; Kreuter, Alexander; Matei, Emil Alexandru; Zhu, Honglin; et al. (Annals of the Rheumatic Diseases, 2024)
Background: The interleukin (IL)-1 receptor accessory protein (IL1RAP) is an essential coreceptor required for signalling through the IL-1, IL-33 and IL-36 receptors. Here, we investigate the antifibrotic potential of the combined inhibition of these cytokines by an anti-IL1RAP antibody to provide a scientific background for clinical development in systemic sclerosis (SSc). Methods: The expression of IL1RAP-associated signalling molecules was determined by data mining of publicly available RNA sequencing (RNAseq) data as well as by imaging mass cytometry. The efficacy of therapeutic dosing of anti-IL1RAP antibodies was determined in three complementary mouse models: sclerodermatous chronic graft-versus-host disease (cGvHD), bleomycin-induced dermal fibrosis model and topoisomerase-I (topo)-induced fibrosis. Results: SSc skin showed upregulation of IL1RAP and IL1RAP-related signalling molecules on mRNA and protein level compared with normal skin. IL-1, IL-33 and IL-36 all regulate distinct gene sets related to different pathophysiological processes in SSc. The responses of human fibroblasts and endothelial cells to IL-1, IL-33 and IL-36 were completely blocked by treatment with an anti-IL1RAP antibody in vitro. Moreover, anti-IL1RAP antibody treatment reduced dermal and pulmonary fibrosis in cGvHD-induced, bleomycin-induced and topoisomerase-induced fibrosis. Importantly, RNAseq analyses revealed effects of IL1RAP inhibition on multiple processes related to inflammation and fibrosis that are also deregulated in human SSc skin. Conclusion: This study provides the first evidence for the therapeutic benefits of targeting IL1RAP in SSc. Our findings have high translational potential as the anti-IL1RAP antibody CAN10 has recently entered a phase one clinical trial.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Fibroblasts; Inflammation; Pulmonary Fibrosis; Scleroderma; Systemic

Comprehensive bone marrow analysis integrating deep learning-based pattern discovery (BMDeep) - Pontones, Martina; Hoefener, H.; Kock, F.; Schwen, L.; Westphal, M.; Dickel, Nicholas; Kunz, Meik; Metzler, Markus (KLINISCHE PADIATRIE, 2022)
Bone marrow morphology forms the basis for the assessment of hematopoiesis. The currently established approach is dependent on manual microscopic counting of a limited number of cells by specially trained personnel, which is inherently associated with substantial intra- and inter-individual variability. The aim of our project is to automatize and improve the evaluation of bone marrow smears and to identify pathological patterns in pediatric leukemia.<br
CRIS-Team WoS Importer:2022-07-08

Effect of Anti-S100A4 Monoclonal Antibody Treatment on Experimental Skin Fibrosis and Systemic Sclerosis–Specific Transcriptional Signatures in Human Skin - Trinh-Minh, Thuong; Györfi, Andrea Hermina; Tomcik, Michal; Tran-Manh, Cuong; Zhou, Xiang; Dickel, Nicholas; Tümerdem, Bilgesu Safak; Kreuter, Alexander; Burmann, Sven Niklas; Borchert, Signe Vedel; Hussain, Rizwan Iqbal; Hallén, Jonas; et al. (Arthritis and Rheumatology, 2024)
Objective: S100A4 is a DAMP protein. S100A4 is overexpressed in patients with systemic sclerosis (SSc), and levels correlate with organ involvement and disease activity. S100A4−/− mice are protected from fibrosis. The aim of this study was to assess the antifibrotic effects of anti-S100A4 monoclonal antibody (mAb) in murine models of SSc and in precision cut skin slices of patients with SSc. Methods: The effects of anti-S100A4 mAbs were evaluated in a bleomycin-induced skin fibrosis model and in Tsk-1 mice with a therapeutic dosing regimen. In addition, the effects of anti-S100A4 mAbs on precision cut SSc skin slices were analyzed by RNA sequencing. Results: Inhibition of S100A4 was effective in the treatment of pre-established bleomycin-induced skin fibrosis and in regression of pre-established fibrosis with reduced dermal thickening, myofibroblast counts, and collagen accumulation. Transcriptional profiling demonstrated targeting of multiple profibrotic and proinflammatory processes relevant to the pathogenesis of SSc on targeted S100A4 inhibition in a bleomycin-induced skin fibrosis model. Moreover, targeted S100A4 inhibition also modulated inflammation- and fibrosis-relevant gene sets in precision cut SSc skin slices in an ex vivo trial approach. Selected downstream targets of S100A4, such as AMP-activated protein kinase, calsequestrin-1, and phosphorylated STAT3, were validated on the protein level, and STAT3 inhibition was shown to prevent the profibrotic effects of S100A4 on fibroblasts in human skin. Conclusion: Inhibition of S100A4 confers dual targeting of inflammatory and fibrotic pathways in complementary mouse models of fibrosis and in SSc skin. These effects support the further development of anti-S100A4 mAbs as disease-modifying targeted therapies for SSc.
CRIS-Team Scopus Importer:2024-05-10

Mutual Amplification of GLI2/Hedgehog and Transcription Factor JUN/AP-1 Signaling in Fibroblasts in Systemic Sclerosis: Potential Implications for Combined Therapies - Bergmann, Christina; Chenguiti Fakhouri, Sara; Trinh-Minh, Thuong; Filla, Tim; Rius Rigau, Aleix Rius; Ekici, Arif Bülent; Merlevede, Benita; Hallenberger, Ludwig; Zhu, Honglin; Dees, Clara; Matei, Alexandru Emil; Auth, Janina; et al. (Arthritis and Rheumatology, 2024)
Objective: Deregulation of the cJUN/AP-1 and hedgehog/GLI2 signaling pathways has been implicated in fibroblast activation in systemic sclerosis (SSc). However, the consequences of their concomitant up-regulation are unknown. Here, we tested the hypothesis that mutual amplification of both pathways might drive persistent fibroblast activation. Methods: Cultured fibroblasts and skin sections of patients with diffuse SSc and healthy volunteers were analyzed. cJUN/AP-1 signaling and hedgehog/GLI2 signaling were inhibited using knockdown and pharmacologic approaches. Hedgehog signaling was activated in mice by fibroblast-specific overexpression of constitutively active Smoothened. Results: cJUN and GLI2 are concomitantly up-regulated and colocalize in fibroblasts of patients with SSc compared to healthy controls. Activation of hedgehog/GLI2 signaling induces the expression of cJUN in vitro and in vivo, whereas inactivation of GLI2 inhibits cJUN expression. Likewise, inactivation of cJUN impairs the expression of GLI2. This mutual regulation occurs at the level of transcription with binding of cJUN and GLI2 to specific binding motifs. Interference with this mutual amplification of cJUN signaling and GLI2 signaling inhibits fibroblast activation and collagen release: Inhibition of cJUN/AP-1 signaling ameliorates hedgehog-induced fibroblast activation and skin fibrosis in SmoACT mice with a reduction of skin thickness of 103% (P = 0.0043) in the treatment group compared to the fibrotic control group. Moreover, combined pharmacologic inhibition of cJUN/AP-1 and hedgehog/GLI2 exerts additive antifibrotic effects in a model of TGFβ-driven experimental fibrosis (TBRACT mice). Conclusion: The transcription factors cJUN and GLI2 reinforce each other's activity to promote fibroblast activation in SSc. Interruption of this crosstalk by combined inhibition of both pathways exerts additive antifibrotic effects at well-tolerated doses.
CRIS-Team Scopus Importer:2024-12-06

Performance of serum biomarkers reflective of different pathogenic processes in systemic sclerosis-associated interstitial lung disease. - Györfi, Andrea Hermina; Filla, Tim; Dickel, Nicholas; Möller, Florian; Li, Yi Nan; Bergmann, Christina; Matei, Alexandru-Emil; Harrer, Thomas; Kunz, Meik; Schett, Georg; Distler, Jörg H.W. (Rheumatology, 2024)
OBJECTIVE: Interstitial lung disease (ILD) is the leading cause of mortality in SSc. Novel biomarkers are crucial to improve outcomes in SSc-ILD. We aimed to compare the performance of potential serum biomarkers of SSc-ILD that reflect different pathogenic processes: KL-6 and SP-D (epithelial injury), CCL18 (type 2 immune response), YKL-40 (endothelial injury and matrix remodelling) and MMP-7 (ECM remodelling). METHODS: Baseline and follow-up serum samples from 225 SSc patients were analysed by ELISA. Progressive ILD was defined according to the 2022-ATS/ERS/JRS/ALAT guidelines. Linear mixed models and random forest models were used for statistical analyses. RESULTS: Serum levels of KL-6 [MD 35.67 (95% CI 22.44-48.89, P < 0.01)], SP-D [81.13 (28.46-133.79, P < 0.01)], CCL18 [17.07 (6.36-27.77, P < 0.01)], YKL-40 [22.81 (7.19-38.44, P < 0.01)] and MMP-7 [2.84 (0.88-4.80, P < 0.01)] were independently associated with the presence of SSc-ILD. A machine-learning model including all candidates classified patients with or without ILD with an accuracy of 85%. The combination of KL-6 and SP-D was associated with the presence [0.77 (0.53-1.00, P' <0.01)] and previous progression of SSc-ILD [OR 1.28 (1.01-1.61, P' =0.047)]. Higher baseline levels of KL-6 [OR 3.70 (1.52-9.03, P < 0.01)] or SP-D [OR 2.00 (1.06-3.78, P = 0.03)] increased the odds of future SSc-ILD progression, independent of other conventional risk factors, and the combination of KL-6 and SP-D [1.109 (0.665-1.554, P < 0.01)] showed improved performance compared with KL-6 and SP-D alone. CONCLUSION: All candidates performed well as diagnostic biomarkers for SSc-ILD. The combination of KL-6 and SP-D might serve as biomarker for the identification of SSc patients at risk of ILD progression.
EVALuna2:538826

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27